2021
DOI: 10.3389/fimmu.2021.685237
|View full text |Cite
|
Sign up to set email alerts
|

Key Macrophage Responses to Infection With Mycobacterium tuberculosis Are Co-Regulated by microRNAs and DNA Methylation

Abstract: Tuberculosis (TB) is the leading cause of death from infection with a single bacterial pathogen. Host macrophages are the primary cell type infected with Mycobacterium tuberculosis (Mtb), the organism that causes TB. Macrophage response pathways are regulated by various factors, including microRNAs (miRNAs) and epigenetic changes that can shape the outcome of infection. Although dysregulation of both miRNAs and DNA methylation have been studied in the context of Mtb infection, studies have not yet investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…In addition, we found reduced KLF10 mRNA levels in mononuclear cells from patients with active TB compared with the levels found in healthy individuals. This agrees with different transcriptomic studies performed in macrophages obtained from lungs of M. tuberculosis-infected mouse models 52,53 and bronchoalveolar lavages [54][55][56] from human individuals, that found reduced KLF10 mRNA levels compared with uninfected mice or healthy individuals, respectively. Reduced KLF10 mRNA levels in cells from patients with active TB active could result from IL-10-mediated negative regulation of the KLF10 gene expression, 57 since it has been shown that mononuclear cells from patients with active TB produce more IL-10 than cells obtained from patients with latent TB or healthy donors upon stimulation with tuberculin.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found reduced KLF10 mRNA levels in mononuclear cells from patients with active TB compared with the levels found in healthy individuals. This agrees with different transcriptomic studies performed in macrophages obtained from lungs of M. tuberculosis-infected mouse models 52,53 and bronchoalveolar lavages [54][55][56] from human individuals, that found reduced KLF10 mRNA levels compared with uninfected mice or healthy individuals, respectively. Reduced KLF10 mRNA levels in cells from patients with active TB active could result from IL-10-mediated negative regulation of the KLF10 gene expression, 57 since it has been shown that mononuclear cells from patients with active TB produce more IL-10 than cells obtained from patients with latent TB or healthy donors upon stimulation with tuberculin.…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, epigenomic modifications are particularly ligated to pathological processes behind the chronic phases of infections, even when the first stages have been overcome [21,22]. Several of these modifications have been described in infectious diseases like viral [23], bacterial [24] and specifically, DNAm changes has been reported in parasitic diseases, such as Malaria, Leishmaniasis and Chagas disease [16,25].…”
Section: Box Plots Of Three Of the Most Interesting Genes Comparing Dnam Levels Between Chronic Chagas Cardiomyopathy Patients (Ccc) And mentioning
confidence: 99%
“…In human cells, it has been shown that 5-AZA has an immunomodulatory function ( 47 ). In addition to insects, it has also been demonstrated in human that DNA methylation can be changed in a short period of time in response to microbial infection and that these changes in DNA methylation can influence immune cell responsiveness ( 48 ), suggesting that microbes, particularly bacteria, use DNA methylation strategies to evade host immune responses ( 49 51 ). A recent study analyzed the global transcriptional patterns of gene expression after M. tuberculosis , and found that the majority of differentially expressed genes were hypermethylated, which could play a biological role in the activation of innate and adaptive immune cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%